Taking the ups and downs at the rollercoaster of love: Associations between major relationship events and the Big Five personality traits - Eva Asselmann; Jule Specht (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Personality predicts how we interact with others, what partners we have, and how happy and lasting our romantic relationships are. At the same time, our experiences in these relationships may affect our personality. Who experiences specific major relationship events and how do these events relate to personality development? We examined this issue based on data from a nationally representative household panel study from Germany (N = 49,932). In this study, the occurrence of major relationship events (moving in with a partner, marriage, separation, and divorce) was assessed yearly and the Big Five personality traits were measured repeatedly in 2005, 2009, 2013, and 2017 with the BFI-S. We applied multilevel analyses to simultaneously model selection effects as well as different types of personality changes in the years before and after these events in the total sample and separately in women and men. Our findings revealed that less agreeable individuals were more likely to experience each of the examined relationship events. Moreover, each event was associated with personality changes, which only occurred after (not before) these events and considerably varied by event and gender. Individuals who moved in with a partner, got married, or separated from a partner primarily experienced changes in openness in the first thereafter, and individuals who separated from a partner or got divorced became less emotionally stable in the following years. However, there was little evidence for 'maturation' effects, except that individuals who moved in with a partner (especially men) became more conscientious in the following years.
Keywords: 330; Personality development; partnership; love; relationship formation; relationship dissolution; longitudinal